Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 2981 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Calotes Cuvier, 1817", "HasGeospatialIssue is false", "HasCoordinate is true" ] } The dataset includes 2981 records from 26 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000931-160822134323880/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences